2014
DOI: 10.1007/s00264-014-2312-3
|View full text |Cite
|
Sign up to set email alerts
|

Gait knee kinematic alterations in medial osteoarthritis: three dimensional assessment

Abstract: Purpose Although kinematic changes in the sagittal plane of the osteoarthritic knee (OA) have been elucidated, very few studies have analysed changes in the frontal and horizontal planes. Therefore, the aim of this study was to investigate in vivo 3D knee kinematics during walking in patients wth knee OA. Methods Thirty patients with medial knee OA and a control group of similarly aged individuals were prospectively collected for this study. All participants were assessed with KneeKG TM system while walking on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
59
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(67 citation statements)
references
References 29 publications
(49 reference statements)
2
59
1
1
Order By: Relevance
“…The smaller range of motion of the obese patients indicated that these individuals use a stiffening knee strategy despite maintaining the knee in more flexion during functional activities [35]. This strategy for reduced range of motion is also found in knee OA patients [1214, 36] and obese individuals without knee pain [8], meaning both extra body weight and pain contribute to the gait pattern change.…”
Section: Discussionmentioning
confidence: 99%
“…The smaller range of motion of the obese patients indicated that these individuals use a stiffening knee strategy despite maintaining the knee in more flexion during functional activities [35]. This strategy for reduced range of motion is also found in knee OA patients [1214, 36] and obese individuals without knee pain [8], meaning both extra body weight and pain contribute to the gait pattern change.…”
Section: Discussionmentioning
confidence: 99%
“…This can be explained by the fact that the patients in the present study had generally lower grades of OA, compared to patients in Bytyqi et al's study. [12] During push-off phase of the gait cycle, results show increased ankle rotations in the frontal and sagittal plane. This support previous findings from Ko, et al (2011) [10] which hypothesized that this increase in sagittal range of motion is a compensatory mechanism in symptomatic knee-OA patient during propulsion to limit the demand on the knee joint to limit onset of symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…The parameters chosen to be extracted were based on variables routinely assessed in clinical biomechanical studies of knee OA populations as proposed in the literature. [12,13,17] These are summarized in Table 2, with acronyms chosen to identify events. The angular kinematic parameters values were extracted for all subjects on MatlabR2015a (The Mathworks, USA) and ANCOVA was performed on SPSS 20.0 (Statistical Package for the Social Sciences).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In such cases, those with knee OA and varus deformity use methods such as toe-out [7] and trunk lean [8] to decrease the external knee adduction moment. Changes in the kinematics and kinetics of the knee joint during the stance phase of gait in patients with knee OA include decreases in the range of motion (flexion-extension) [9] and in the vertical component of the ground reaction forces [10]. These changes are compensatory tactics in order to decrease knee pain during the stance phase.…”
Section: Introductionmentioning
confidence: 98%